Mother’s education, age and knowledge about home accident prevention– A relational approach - Rajesh Salvi, Jayashree (Indian Journal of Nursing Sciences, 2024)
This review considers barriers to, and facilitators of, success for interventions to reduce unintentional injury to children in the home through supply and/or installation of home safety equipment, and looks at risk assessments. This paper examines the effect of mother education on prevention of home accident among children's domestic accidents. Systematic reviews of qualitative research, bibliographic databases searched for studies on interventions to reduce unintentional child injury in the home, or on related attitudes and behaviors. Studies were quality appraised, findings extracted, and a conceptual framework was developed to assess factors affecting the success of interventions. Nine peer-reviewed journal articles were included. Barriers and facilitators highlighted at organizational, environmental and personal levels. Effective provision of safety equipment involves ongoing support with installation and maintenance. Take up and success of interventions depends on adjusting interventions according to practical limitations and parents‟ cultural expectations. A particular barrier was parents‟ inability to modify rented or shared accommodation. This review highlights ways, in which health inequalities affects the take up and success of home safety interventions, and how health workers can use this knowledge to facilitate future interventions. The way social deprivation defined in different studies varied considerably. The literature not evenly spread across different injury types and does not reflect the burden of injury. There is a paucity of evidence relating to the prevention of child pedestrian injury. Very few studies examined the impact of interventions in different social groups. Without such evidence, it remains difficult for those involved in health promotion to know how to design and target interventions to address inequalities in child injury rates.